2022
DOI: 10.1371/journal.pone.0271612
|View full text |Cite
|
Sign up to set email alerts
|

Which interventions may improve bracing compliance in adolescent idiopathic scoliosis? A systematic review and meta-analysis

Abstract: This review aimed to systematically review and meta-analyze the effects of interventions in improving bracing compliance among adolescent idiopathic scoliosis (AIS) patients. Eight databases were searched from their inception to April 2022. The eligibility criteria included controlled studies that used any type of intervention to enhance bracing compliance in braced AIS patients. Two researchers independently screened articles and extracted data based on the PICO (participant, intervention, comparator, and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 79 publications
0
17
0
1
Order By: Relevance
“…The review found that actual compliance to the orthotic treatment was generally lower than the prescribed wearing time and exhibited wide variation due to the heterogeneities of calculation period, measurement methods, and orthosis prescription time. More importantly, electronic compliance monitors show promise in regular orthotic treatment not only because of their high reliability 36,37 but also due to their effectiveness in improving compliance 17,38,39 . For example, Morton et al found that objective monitor recorded the patients' compliance to the orthosis as 47% of the prescribed time, while the subjective compliance reported by physicians, orthotists, parents, and patients were 64%, 66%, 72%, and 75%, respectively 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The review found that actual compliance to the orthotic treatment was generally lower than the prescribed wearing time and exhibited wide variation due to the heterogeneities of calculation period, measurement methods, and orthosis prescription time. More importantly, electronic compliance monitors show promise in regular orthotic treatment not only because of their high reliability 36,37 but also due to their effectiveness in improving compliance 17,38,39 . For example, Morton et al found that objective monitor recorded the patients' compliance to the orthosis as 47% of the prescribed time, while the subjective compliance reported by physicians, orthotists, parents, and patients were 64%, 66%, 72%, and 75%, respectively 40 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the improvement in brace compliance might ironically play a role in decreasing scores. The routine introduction of sensors into scoliosis braces, which took place at our institution ubiquitously around 2010, has been shown to improve brace compliance [ 21 ]. However, bracing has unfortunately been linked to lower SRS scores in both the activity and self-image domains [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the duration of brace wear is an important factor in treatment outcomes, but patient compliance will in uence the duration of brace wear. Causes of nonadherence are related to the adverse effects of brace therapy, such as a negative cosmetic appearance, functional discomfort at pressure points, hot weather, exercise limitations, emotional discomfort, and impact on quality of life may all be important reasons for adherence [10]. Meanwhile, the psychological impact of long-term brace wear on adolescents cannot be ignored [11].…”
Section: Introductionmentioning
confidence: 99%